2008
DOI: 10.1103/physrevd.77.103507
|View full text |Cite
|
Sign up to set email alerts
|

Testing cosmology with cosmic sound waves

Abstract: Wilkinson Microwave Anisotropy Probe (WMAP) observations have accurately determined the position of the first two peaks and dips in the cosmic microwave background (CMB) temperature power spectrum. These encode information on the ratio of the distance to the last scattering surface to the sound horizon at decoupling. However prerecombination processes can contaminate this distance information. In order to assess the amplitude of these effects, we use the WMAP data and evaluate the relative differences of the C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 59 publications
1
40
0
Order By: Relevance
“…These two parameters capture most of the constraining power of the WMAP data for dark energy properties (Wang & Mukherjee 2007;Wright 2007;Elgarøy & Multamäki 2007;Corasaniti & Melchiorri 2008), with one important difference. The distance prior does not capture the information on the growth of structure probed by the late-time ISW effect.…”
Section: Wmap Distance Priormentioning
confidence: 99%
“…These two parameters capture most of the constraining power of the WMAP data for dark energy properties (Wang & Mukherjee 2007;Wright 2007;Elgarøy & Multamäki 2007;Corasaniti & Melchiorri 2008), with one important difference. The distance prior does not capture the information on the growth of structure probed by the late-time ISW effect.…”
Section: Wmap Distance Priormentioning
confidence: 99%
“…[22][23][24] have studied this point in more detail and found that the constraints on R are relatively stable under minor modifications of the dark energy parameters underlying the analysis, including dark energy clustering [24]. It was found that massive neutrinos had a larger effect on R (few percent level) [24]. In Ref.…”
Section: Cmb Measurementsmentioning
confidence: 97%
“…We specifically use the CMB-only bandpowers described in this paper and available in the Planck Legacy Archive 24 , adopting the same weighting scheme within each bin. Fitting for the positions and amplitudes of features in the band-powers is a topic with a long history, with approaches becoming more sophisticated as the fidelity of the data improved (e.g., Scott & White 1994;Hancock & Rocha 1997;Knox & Page 2000;de Bernardis et al 2002;Bond et al 2003;Page et al 2003;Benoît et al 2003;Durrer et al 2003;Readhead et al 2004;Jones et al 2006;Hinshaw et al 2007;Corasaniti & Melchiorri 2008;Pryke et al 2009). Following earlier approaches, we fit Gaussian functions to the peaks and troughs in C T T and C EE , but parabolas for the C TE features.…”
Section: Appendix D: High-likelihood Supplementmentioning
confidence: 99%